The potential use of natural products to negate hepatic, renal and neuronal toxicity induced by cancer therapeutics - YALÇIN, AHMET SUHA; YILMAZ, BETÜL (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
Different types of chemotherapeutics are used for cancer treatment. These drugs act on several signal pathways, lead to programmed cell death, and damage cancer cells. Although many specific mechanisms of action have been suggested for chemotherapeutics, there are still gaps in understanding their effects. They may affect different components of the cell, particularly proteins with specific functions, such as enzymes. Recently, targeted and immuno therapies were introduced for treatment of different cancers. However, many cancer patients still depend on traditional and well-known drugs. Doxorubicin and platinum-based drugs are among the most frequently used chemotherapeutics. They are highly cytotoxic for cancer cells, but they also act on healthy cells. Hence, it is crucial to understand the mechanisms involved in order to decrease their side effects. Natural products, many of which are also available over-the-counter, may be considered to decrease various cancer drug-induced side effects. This review focuses on the use of these compounds to overcome side effects of chemotherapeutics, primarily doxorubicin and cisplatin, in the liver, kidney, and neuronal systems.
Keywords: Doxorubicin; Cisplatin; Hepatotoxicity; Nephrotoxicity; Neurotoxicity; CISPLATIN-INDUCED NEPHROTOXICITY; DOXORUBICIN-INDUCED HEPATOTOXICITY; INDUCED PERIPHERAL NEUROPATHY; OXIDATIVE STRESS; N-ACETYLCYSTEINE; VITAMIN-E; FULLERENOL C-60(OH)(24); IN-VIVO; MITOCHONDRIAL DYSFUNCTION; INDUCED CARDIOTOXICITY